2019
DOI: 10.4034/pboci.2019.191.78
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cavity Dimensions on Microleakage of Two Bulk-Fill Composite Resins

Abstract: Objective: To evaluate the effect of cavity dimensions on the amount of microleakage in two different types of bulk-fill composite resins. Material and Methods: Forty class II cavities were prepared in the mesial and distal surfaces of human molars without any carious lesions. The samples were divided into 4 groups (n=10): Group 1: cavities with 3 mm of buccolingual width (known as the smaller cavity), filled with Tetric N-Ceram Bulk Fill composite resin; Group 2: cavities with 6 mm of buccolingual width (larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…In such a case, the C-factor is high, 34 and therefore possibility of gap formation and adhesive bond failure. 35 Another possible explanation could be related to ineffective or inadequate curing at the deeper layer of the composite restoration. 36 Our findings were in line with previous studies that demonstrated that the placement of a large increment of bulk-fill resin composite into a cavity increased the potential of creating high shrinkage stress and induced more strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a case, the C-factor is high, 34 and therefore possibility of gap formation and adhesive bond failure. 35 Another possible explanation could be related to ineffective or inadequate curing at the deeper layer of the composite restoration. 36 Our findings were in line with previous studies that demonstrated that the placement of a large increment of bulk-fill resin composite into a cavity increased the potential of creating high shrinkage stress and induced more strain.…”
Section: Discussionmentioning
confidence: 99%
“…36 Our findings were in line with previous studies that demonstrated that the placement of a large increment of bulk-fill resin composite into a cavity increased the potential of creating high shrinkage stress and induced more strain. 35,37 This is because the buccal and lingual walls are pulled together which might cause adhesive failure and enhanced microleakage. 35,37 Our results coincided with Özel and Syman, 2009, 38 Giachetti et al, 2006, 14 who suggested that using layering or increment techniques in Class II cavities reduces the adverse effects of polymerization shrinkage and marginal gap formation comparing to the bulk technique.…”
Section: Discussionmentioning
confidence: 99%
“…Keberhasilan klinis dari restorasi resin komposit sangat bergantung pada ikatan dan adaptasi material dengan dinding kavitas. 46 Sebelum reaksi polimerisasi dilakukan, molekul-molekul monomer memiliki jarak kurang lebih 0,3 -0,4 nm. Monomer-monomer yang terpisah oleh Van Der Waals Radius tersebut akan bergerak dan saling berdekatan satu sama lain dengan jarak 0,15 nm ketika polimerisasi dan menghasilkan pengerutan yang menyebabkan kebocoran mikro.…”
Section: Kebocoran Mikrounclassified
“…Kavitas dengan dimensi yang luas akan memperbesar risiko kebocoran mikro karena adanya peningkatan c-factor pada kavitas tersebut, hal itu sangat berkaitan dengan aplikasi resin komposit bulk fill pada kavitas yang luas. 46 Beberapa cara seperti modifikasi bahan komposit oleh produsen yang menghasilkan bahan bulk fill rendah shrinkage, tingkat translusensi yang sesuai, serta pengembangan curing unit harus diimplementasikan oleh dokter gigi melalui prosedur restoratif yang adekuat untuk mengurangi risiko kebocoran mikro. 25…”
Section: Kebocoran Mikrounclassified
“…Creation of microleakage at marginal areas will pave the way for secondary caries, enamel cracks, staining of restoration and post-operative sensitivity [1] In addition to these kinds of restorations, bleaching of discoloured teeth is becoming a common and popular treatment in dentistry as this approach is the most conservative and favorable procedure to improve the aesthetic appearance of teeth compared to other techniques [2]. For more durable results, bleaching of the vital teeth is usually carried out using the office bleaching followed by home bleaching techniques.…”
Section: Introductionmentioning
confidence: 99%